Influence of granitic rock fines addition in the alkali-aggregate reaction (AAR) in cementitious materials - Santos,Bruna Silva (2021)
Abstract According to previous studies, fine materials originated from reactive aggregates can act as a Alkali-Aggregate Reaction mitigator, having its effectiveness dependent on their reactivity, fineness and added content. Thus, the present work aims to study if reactive granitic rock fines can mitigate or reduce the AAR and how the fineness of the material influences its mitigation capacity. For this purpose, granitic rock fines (GRF) from 2 different deposits and Pyrex glass fines (PGF) were tested as concrete addition. Each one of these fines were used in two different finesses and added to the concrete in the contents of 20% by mass of cement. It was observed that the addition of GRF did not affect the physical-mechanical properties of concrete and allowed the reduction in the AAR, being more accentuated with the increase of its specific surface.